Edgar Allan Poe and Charles Baudelaire’s aesthetic architecture of revolt: an axial analysis - Isaak, Sonya (American studies, 2021)
Cover -- Titel -- Imprint -- Contents -- Acknowledgments -- Introduction -- Poedelairian Aesthetics: The State of Critical Inquiry -- An Axial Methodology: Writing as an Architecture of Space and Time -- Precursor Axial Models in Structural and Post-structural Theories -- Part One: Exploring the Context -- I Edgar Allan Poe's American Identity in Question -- 1 A Biographical Sketch -- 2 The United States and the Literary Climate in the Early Nineteenth Century -- 3 Poe and his Contemporaries -- 4 Poe's Reception -- II Baudelaire's Polyglot Identity -- 1 A Biographical Sketch -- 2 France in the Early Nineteenth Century -- 3 Baudelaire and his Contemporaries -- III Baudelaire's Fascination with Poe -- 1 Baudelaire's Essays on Poe -- Part Two: Exploring the Aesthetic Affinities of Poe and Baudelaire -- I The Anti-Mimetic Art of Imaginative Recollection (Inventatio over Imitatio) -- II "L'Art pour l'Art" and Poetry for Poetry -- III The Aesthetics of Self-Invention -- 1 Daguerreotypes and Self-Representation -- 2 Anonymous and Pseudonymous Experiments with Identity -- 3 Fictional Autobiography and Literary Travesty -- 4 Common Aesthetic Poses -- 5 Dandyism -- 6 Non-Conformism: Revolt Against the Socio-Political Mainstream -- IV Constructing an Aesthetic Ideal -- 1 Poe's "Lenore": Romanticism Revisited or Revised? -- 2 The Baudelairian Revision of Romanticism and Quest for an Aesthetic Ideal -- V An Architecture of Aesthetic Spaces -- 1 Le monde intérieur versus le monde extérieur -- 2 Aesthetic Revolt: The Individual (or the Artist) against Society -- 3 Temporal Conflict: Limited Time and Eternity -- VI Existential Conflict in the Quest for the Ideal -- 1 Spleen and Ideal in Baudelaire's Writing -- 2 Spleen -- 3 Man's Odyssey in his Pursuit of the Ideal -- 4 The Failed Ideal and the Dominance of Spleen -- 5 "Spleen Et/Est idéal.